2021
DOI: 10.1093/eurpub/ckab075
|View full text |Cite
|
Sign up to set email alerts
|

Post-implementation perspectives on smokefree prison policy: a qualitative study with staff and people in custody

Abstract: Background A comprehensive smokefree prison policy (SFPP) was introduced in Scottish prisons from November 2018, reflecting concern about inequalities in occupational exposures to second-hand smoke (SHS) and tobacco-related harms among people in custody (PiC). We aimed to address a gap, whereby few studies have sought to understand SFPP from the perspectives of people living and working in prisons. Methods As part of a compre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…The relationship may initially appear to mirror the normal characteristics of a free person-general practitioner relationship, but, in reality, it is subject to the self-serving use of medical, pharmacological, and welfare resources available to prisoners. The prison context inevitably obliges prisoners to adhere to internal rules and even procedures for which prison benefits may legitimately be requested [15].…”
Section: Therapeutic Alliance and Consent To Treatmentmentioning
confidence: 99%
“…The relationship may initially appear to mirror the normal characteristics of a free person-general practitioner relationship, but, in reality, it is subject to the self-serving use of medical, pharmacological, and welfare resources available to prisoners. The prison context inevitably obliges prisoners to adhere to internal rules and even procedures for which prison benefits may legitimately be requested [15].…”
Section: Therapeutic Alliance and Consent To Treatmentmentioning
confidence: 99%
“…[25][26][27] Findings from TIPs interviews exploring postimplementation perspectives on Scotland's smoke-free prison policy among a separate sample of staff and PiC also suggest that the smoke-free prison policy may have contributed to changes in the use of NPS, specifically through misuse of e-cigarettes. 9 Understandings of the general risks posed by e-cigarettes for illicit drug taking, including NPS, are developing: a 2018 systematic review 28 suggested several potential areas of risk. These include: that e-cigarettes might be viewed as a 'safer and innocuous method to experiment and try drugs'; levels of illicit drug use might increase due to the ease with which e-cigarettes can be used for drug delivery; the emergence of new patterns of drug use; and illicit drug use may be easier to conceal, leading to increased problems with detection by authorities and greater risks of 'unintended or malicious' exposures to bystanders (p107).…”
Section: Discussionmentioning
confidence: 99%
“…5 Complementary qualitative research suggests this broad support for e-cigarettes in Scottish prisons has been substantially influenced by perceptions that they are beneficial in helping PiC and staff to cope with the major operational change represented by the removal of tobacco. 9 Favourable perceptions of e-cigarettes in Scottish prisons also reflect broader evidence on their appeal and effectiveness for some current and ex-smokers (eg, those who feel unwilling or unable to quit nicotine) 10 11 and evidence on reduced harms to users and bystanders from vaping relative to smoking. 12 However, important issues and challenges in relation to permitting PiC to vape were also voiced by prison staff and some PiC in anticipation of their introduction, 1 13 as well as by commentators in other jurisdictions.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
See 1 more Smart Citation
“…For those prisoners who do not smoke, exposure to SHS also threatens to impede upon civil rights [4], while for prisoners who smoke, introducing a complete ban may further strip away the few remaining individual rights and privileges. Interventions to tackle tobacco use and second-hand smoke exposure can be challenging to implement, with concerns voiced that limiting access to tobacco products can lead to increased violence in prison setting, albeit evidence to validate this concern is mixed, and there are reports of reductions in violence following implementation [14][15][16].…”
Section: Introductionmentioning
confidence: 99%